Pengaruh Pembelajaran Pendidikan Pancasila Terhadap Penerapan Sikap Egalitarian Peserta Didik di Sma Negeri 1 Seputih Surabaya - Imelda Mauly Jevita; Berchah Pitoewas; Rohman Rohman; Devi Sutrisno Putri (Jurnal Pendidikan Sosial Dan Konseling, 2026)
Pancasila Education learning has a strategic role in shaping the character of students who respect diversity, uphold equality, and reject discrimination. However, in school life, various forms of social interactions are still found that do not fully reflect an egalitarian attitude. This condition shows the importance of Pancasila Education learning as a means of instilling the values of equality in students' lives. This study aims to determine the effect of Pancasila Education learning on the implementation of egalitarian attitudes of students at SMA Negeri 1 Seputih Surabaya and to answer the question of the extent to which Pancasila Education learning contributes to shaping students' egalitarian attitudes. This study uses a descriptive method with a quantitative approach. The research sample consisted of 74 grade XI students selected using a random sampling technique. Data collection was carried out through questionnaires, observations, and documentation. The data obtained were analyzed using descriptive statistics and simple linear regression to determine the effect of Pancasila Education learning variables on students' egalitarian attitudes. Pancasila Education learning variables were measured through indicators of material, strategies, and learning methods, while egalitarian attitudes were measured through indicators of respecting diversity, rejecting discrimination, and equality in school activities. The results of the study indicate that Pancasila Education learning and students' egalitarian attitudes are both in the moderate category. Furthermore, Pancasila Education learning has a positive and significant effect on students' egalitarian attitudes. These findings indicate that Pancasila Education learning plays a role in instilling Pancasila values and shaping students' egalitarian attitudes, reflected in respect for diversity, rejection of discrimination, and the implementation of equality in school life.